Biosphere Reserves in the Southwest of Ethiopia - Semegnew Tadese; Teshome Soromessa; Tesefaye Bekele; Brhane Meles (Advances in Agriculture)
Forests that have a wide ecological gradient, diversity, and significant cover are confined in the southwestern part vis-à-vis other parts of Ethiopia, while the country is fronting biodiversity losses. The intention of this paper is comparative assessment of Majang, Kafa, Sheka, and Yayo biosphere reserves, located in the southwest of Ethiopia, regarding their status of plant diversity, challenges, and efforts of conservation. To this end, an extensive review of different journals, articles, and proceedings was made. Relevance to the objectives of the review was a selection criterion for sources inclusion. Consequently, the review indicates that all the biosphere reserves contained myriad plant biodiversity, specifically the “hotspot” of Afromontane rainforest biodiversity, with some degree of dissimilarities among them. For instance, the values of Shannon index illustrated a decreasing order in plant diversity as Sheka followed by Kafa, Yayo, and Majang biosphere reserve. Besides, out of the top ten documented plant families, the species richest families are Rubiaceae (15) in Yayo, Asteraceae (12) in Kafa, Euphorbiaceae (11) in Majang, and Asteraceae (11) in Sheka biosphere reserve, while the least species found in the families are as follows: Aspleniaceae and Sapindaceae in Majang; Poaceae, Solanaceae, and Araceae in Sheka; Celastraceae and Piperaceae in Kafa; and Fabacae and Solanaceae in Yayo. However, many challenges were encountered in all the biosphere reserves. The driving force behind is commercial coffee-tea plantation, agriculture expansion, overgrazing, firewood, charcoal, and other factors. Hence, to reduce forest conversion and biodiversity loss, the government of Ethiopia is creating conservation mechanism like the establishment of the protected area and biosphere reserve which is controlled and managed by the community and the government.